Breathable and antibacterial EVA foam material and preparation method thereof
By loading MnO2 and "CS/AgNPs" nanoparticles on graphene oxide, combined with specific preparation methods, the problem of poor antibacterial effect of traditional EVA foaming materials is solved, and high-efficiency antibacterial and good breathability EVA foaming materials are achieved.
Patent Information
- Application Number
- CN202510230967.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-28
AI Technical Summary
Traditional EVA foaming materials are easily used for bacterial reproduction during long-term use or outdoor environments, resulting in poor antibacterial effects.
By loading MnO2 and "CS/AgNPs" nanoparticles on graphene oxide (GO), GO-SH/MnO2/CS/AgNPs composite materials were constructed, and the open-pore and breathable EVA foaming material was prepared by combining the secondary foaming method and the crystallization temperature difference method.
It realizes the material's efficient antibacterial properties and good breathability, and improves the air circulation efficiency and stability of the material in actual applications.
Smart Images

Figure CN119875238A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a breathable and antibacterial EVA foam material and a preparation method thereof. Background Art
[0002] EVA is characterized by good softness, rubber-like elasticity, good flexibility at -50°C, transparency and surface gloss, good chemical stability, good anti-aging and ozone resistance, and non-toxicity. It has good miscibility with fillers, coloring and molding processability. EVA is widely used in foamed shoe materials, films, packaging films, hot melt adhesives, wires and cables, toys and other fields. In the EVA resin used in shoe materials, the vinyl acetate content is generally 15% to 22%. Because EVA resin blended foam products have the properties of softness, good elasticity, and chemical corrosion resistance, they are widely used in the soles and interior materials of mid-to-high-end tourist shoes, hiking shoes, slippers, and sandals. In addition, this material is also used in the fields of sound insulation boards, gymnastics mats and sealing materials. However, items such as shoe materials and gymnastics mats inevitably need to have direct contact with various outdoor locations for a long time, which will provide opportunities for the growth of various bacteria on them. Therefore, the research of EVA foam materials with antibacterial properties is of great value for its application in shoe materials and other fields.
[0003] The traditional method to improve the antibacterial properties of polymer materials is to directly add traditional antibacterial agents such as nano zinc oxide, nano silicon dioxide, chitosan, etc., and melt blend these antibacterial additives directly with the matrix. However, most nano metal oxides and other antibacterial agents are strongly hydrophilic materials, while most polymer materials are hydrophobic materials, which leads to poor compatibility of these antibacterial additives with the matrix and cannot be stably and evenly distributed in the matrix, resulting in poor overall antibacterial effect of the product.
[0004] Chitosan (CS) particles have good antibacterial properties. Chitosan is a product of the natural polysaccharide chitin with some acetyl groups removed. It has multiple physiological functions such as biodegradability, biocompatibility, non-toxicity, antibacterial, anti-cancer, lipid-lowering, and immune enhancement. It is widely used in antibacterial agents, medical fibers, medical dressings, artificial tissue materials, drug sustained-release materials, gene transduction vectors, biomedical fields, medical absorbable materials, and many other fields. Metal nanomaterials mainly include gold nanoparticles, silver nanoparticles, copper nanoparticles, and metal oxide nanoparticles. Among them, silver nanoparticles AgNPs have attracted much attention for their broad-spectrum antibacterial ability by destroying bacterial cell membranes and intracellular components.
[0005] Based on this, the present invention proposes a breathable and antibacterial EVA foam material and a preparation method thereof. Summary of the invention
[0006] The invention uses a secondary foaming method and a crystallization temperature difference method to make an EVA foam material into an open-cell structure. The cells of the open-cell polymer foam material are interconnected, and the gas phase and the polymer phase in the polymer foam body are continuous phases, and the fluid can pass through the foam body. The ease of fluid passing is affected by the characteristics of the polymer itself and the degree of open cells. The product improves the air circulation efficiency in practical applications and has a better ventilation effect.
[0007] The present invention loads MnO2 and "CS / AgNPs" nanoparticles on graphene oxide (GO) with large specific surface area and lasting stability to construct a "GO-SH / MnO2 / CS / AgNPs" composite material for antibacterial use. Thiol-functionalized graphene oxide (GO-SH) is a good nanomaterial support matrix, wherein "-SH" represents a thiol group. The nanoparticles are uniformly distributed on the surface of the support matrix through the interaction between the thiol group and the CS / AgNPs nanoparticles. The construction of the composite material can utilize the biocompatibility, surface roughness and morphology of the support matrix to improve the antibacterial properties of the nanoparticles. The "GO-SH / MnO2 / CS / AgNPs" composite material constructed in this way has higher antibacterial activity and better stability.
[0008] The object of the present invention is to provide an EVA foam material having both air permeability and antibacterial properties and a preparation method thereof.
[0009] To achieve the above object, the present invention adopts the following technical solutions: The invention discloses an open-cell, breathable and antibacterial EVA foam material. The raw materials include, by weight: 70 parts of EVA (ethylene-vinyl acetate), 20 parts of LDPE (low-density polyethylene), 10 parts of POE-g-MAH (maleic anhydride grafted polyolefin elastomer), 1-3 parts of composite antibacterial additive, 2.5 parts of AC foaming agent, 1.5 parts of cross-linking agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant and 0.2 parts of release agent.
[0010] Furthermore, the composite antibacterial adjuvant is GO-SH / MnO2 / CS / AgNPs. The POE-g-MAH preparation steps include: weighing 0.4 parts by weight of maleic anhydride MAH, dissolving MAH in acetone to prepare a solution. Weighing 4 parts by weight of polyolefin elastomer POE particles, spraying the MAH acetone solution into the POE particles, and mixing them evenly in a high-speed mixer, and standing to volatilize the acetone. The mixture is melt-blended for 10 minutes using a torque rheometer, with a rotor speed of 30r / min and a torque temperature of 165°C. After blending, the melt is refined into sheets in an open mill.
[0011] Furthermore, the preparation steps of the composite antibacterial additive (GO-SH / MnO2 / CS / AgNPs) include: (1) Preparation of graphene oxide (GO): 0.5 g of graphite powder and 24 mL of H2SO4 solution were stirred at room temperature for about 2 h. Then, the mixture was cooled to 3 °C and 1.2 g of KMnO4 was slowly added to the mixture. Next, the mixture was heated to 30-35 °C and stirred for 24 h. Then, 20 mL of deionized water was added to the mixture and stirred for 5 min. Finally, 10 mL of distilled water and 5 mL of 30 wt% H2O2 solution were added to the mixture to complete the reaction. The resulting mixture was washed with a 5 wt% HCL deionized water solution until the pH reached 5-6 and GO was obtained after vacuum drying at 50 °C for 24 h.
[0012] (2) Preparation of GO-SH / MnO2: First, 5.0 g of 4-aminothiophenol and 80 mL of 1 M HCl solution were added to a three-necked flask, and the reaction temperature was raised to 50 °C under stirring until 4-aminothiophenol was completely dissolved. Then, NaNO2 solution (10.0 g of NaNO2 dissolved in 100 mL of deionized water) was added dropwise to the reaction mixture under ice bath conditions until the bubbles disappeared completely. After that, 5.0 g of GO was dispersed in 200 mL of deionized water and then added to the above solution. After stirring for 12 h under ice bath, the mixture was washed with acetone, ethanol and deionized water. Finally, GO-SH was obtained by vacuum drying at 50 °C for 24 h. 2.0 g of GO-SH was ultrasonically dispersed in 100 mL of pure water, 20 mL of potassium permanganate solution (15 mg / L) was added dropwise under stirring, and then 12 mL of formamide was added and ultrasonicated for 30 min. The precipitate was collected by centrifugation, washed three times with pure water, and dried in an oven for 12 h to obtain GO-SH / MnO2.
[0013] (3) Preparation of CS / AgNPs: 2 g CS was dissolved in 200 mL acetic acid aqueous solution (0.1 wt%) and stirred in an oil bath. During the stirring process, 10 mL of freshly prepared 5 mg / mL AgNO3 solution was added dropwise. After stirring and heating to 95 °C, 0.1 g / mL NaOH solution was added dropwise until the solution turned yellow. The reaction was terminated after stirring at 95 °C for 20 min. The precipitate was collected by centrifugation, and the product was washed three times with deionized water. The product was then dried in vacuo at 60 °C for 1 h to obtain CS / AgNPs.
[0014] (4) Preparation of GO-SH / MnO2 / CS / AgNPs: GO-SH / MnO2 was dispersed in deionized water, and then CS / AgNPs were added to the suspension with a mass ratio of GO-SH / MnO2 and CS / AgNPs of 1:2. The suspension was magnetically stirred at room temperature for 5 h, and then the mixture was washed three times with deionized water. After centrifugation, the product was vacuum dried at 70 °C for 12 h to obtain GO-SH / MnO2 / CS / AgNPs.
[0015] Furthermore, the EVA foam material is an open-cell structure, and the preparation steps include: melt-blending EVA and LDPE, two materials with a large difference in crystallization temperatures, wherein the melt structure contains two blended polymers with different crystallization temperature values, and the high crystallization temperature polymer will crystallize before the low crystallization temperature polymer, thereby generating pressure on the pore structure to cause the pores to rupture and connect to form an open-cell structure, and at the same time, using a secondary foaming method as a compression foaming method to make the EVA foam material into an open-cell pore structure.
[0016] Furthermore, the preparation method of the breathable and antibacterial EVA foam material is as follows: 70 parts of EVA (ethylene-vinyl acetate), 20 parts of LDPE (low-density polyethylene), 10 parts of POE-g-MAH (maleic anhydride modified polyolefin elastomer), 1-3 parts of composite antibacterial additive, 2.5 parts of AC foaming agent, 1.5 parts of cross-linking agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant, and 0.2 parts of release agent are put into an internal mixer for blending, and then the blended product is subjected to cold and hot compression molding; specifically comprising the following steps: (1) EVA, POE-g-MAN, LDPE and crosslinking agent were placed in a preheated internal mixer at 130°C and blended for 10 min at a speed of 30 rpm; (2) adding the composite antibacterial auxiliary agent, AC foaming agent, filler, calcium zinc stabilizer, lubricant, and release agent to the blend obtained in step (1), and continuing to mix in an internal mixer at 130° C. for 10 min; (3) The blend obtained in step (2) is pressed into a thin sheet by an open mill and then transferred into a flat vulcanizer for compression foaming. The upper and lower mold plate temperatures are both set to 150° C., the pressure is 10 MPa, and the compression time is 600 s. Pre-foaming is performed once. The pre-foamed semi-finished product is placed in a 60° C. forced air drying oven and dried for 12 h. Then, the upper and lower mold plate temperatures are both adjusted to 175° C., the pressure is 15 MPa, and the compression time is 380 s. Secondary foaming is performed. After the mold is opened, the breathable and antibacterial EVA foam material automatically pops out.
[0017] The filler is one or more of nano zinc oxide and zinc stearate; The cross-linking agent is dicumyl peroxide; The lubricant is one or more of stearic acid, butyl stearate and oleamide.
[0018] Preferably, the filler is nano zinc oxide; the lubricant is stearic acid; and the release agent is paraffin.
[0019] The beneficial effects of the present invention are: The present invention uses the crystallization temperature difference method to melt blend EVA (crystallization temperature 10°C) and LDPE (crystallization temperature 90°C), two materials with large crystallization temperatures. Two semi-crystalline polymers with different crystallization temperatures are melt blended to maximize the stiffness contrast between the hard and soft regions in the polymer matrix. Since the cell opening process occurs after the foam extrudate leaves the die, the foam structure is naturally cooled by the surrounding air. If the melt structure has two materials with different T c The value of the polymer blend is high T c The polymer will precede the low T c The polymer crystallizes. This means that at two T c Value between, soft section (ie low T c polymers) are almost like liquids, while hard sections (i.e. high T c The polymer is almost solid-like, resulting in a large stiffness contrast. If the cell opening process occurs at a temperature between two T c When the value is between 0.01 and 0.17, the chance of cell opening will be greatly increased due to the large difference in stiffness. There are two blended polymers with different crystallization temperature values in the melt structure. The high crystallization temperature polymer will crystallize before the low crystallization temperature polymer, thereby exerting pressure on the cell structure to cause the cells to break and connect to form an open-cell structure. At the same time, the secondary foaming method is used as the compression foaming method to make the EVA foam material into an open-cell cell structure. Since the open-cell cell structure is interconnected, the air circulation efficiency is improved and its air permeability is enhanced.
[0020] The invention adopts GO-SH / MnO2 / CS / AgNPs as a composite antibacterial agent to prepare a highly effective antibacterial EVA foam material, which has a scientific and reasonable formula and a simple and practical process flow. The heterogeneous structure of CS encapsulating AgNPs can enhance the oxygen vacancy concentration, oxygen storage capacity and redox activity of the material. CS / AgNPs are loaded with GO-SH to promote their uniform distribution in the mass and improve the antibacterial performance.
[0021] The invention adds a low content of two-dimensional nanofillers to the matrix, which is an effective strategy to improve the antibacterial properties of polymers. Because they have excellent ability to penetrate bacterial biofilms, GO and CS / AgNPs are selected to construct a composite antibacterial material. In addition, the construction of the composite material can also utilize the biocompatibility, surface roughness and morphology of the supporting matrix to improve the antibacterial properties of the nanoparticles so that they have higher antibacterial activity and better stability. Among them, in view of the efficiency and uniformity of the loading of nano CS / AgNPs on the GO surface, GO-SH is obtained by functionalizing GO with thiol groups, making GO a good nanomaterial supporting matrix. Through the interaction between the thiol group and the CS / AgNPs nanoparticles, the CS / AgNPs nanoparticles are uniformly distributed on the surface of the GO-SH supporting matrix. In addition, there is a large amount of H2O2 in the microenvironment of bacterial infection. Since MnO2 is an effective catalyst that triggers the decomposition of H2O2 into H2O and O2, the invention uses MnO2 to synergistically fight bacteria, and MnO2 can decompose the environment that is conducive to bacterial growth. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the Fourier infrared image of the composite antibacterial adjuvant of Example 1; Figure 2 This is a scanning electron microscope image of the composite antibacterial adjuvant of Example 1; Figure 3 is a scanning electron microscope image of the pores of Example 1; Figure 4 Schematic diagram of antibacterial test. DETAILED DESCRIPTION
[0023] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0024] The raw material parts used in the following examples and comparative examples are parts by weight; the crystallization temperatures of the EVA and LDPE used are 10° C. and 90° C., respectively.
[0025] Example 1 (1) Preparation of polymer matrix: 70 parts of EVA, 20 parts of LDPE, 10 parts of POE-g-MAH, and 1.5 parts of cross-linking agent were placed in an internal mixer preheated at 130°C and blended for 10 min at a speed of 30 rpm; (2) Preparation steps of composite antibacterial additive GO-SH / MnO2 / CS / AgNPs: (2-1) Preparation of graphene oxide GO: 0.5 g of graphite powder and 24 mL of concentrated H2SO4 solution (70 wt%) were stirred at room temperature for about 2 h. Then, the mixture was cooled to 3 °C and 1.2 g of KMnO4 was slowly added to the mixture. Next, the mixture was heated to 30 °C and stirred for 24 h. Then, 20 mL of deionized water was added to the mixture and stirred for 5 min. Finally, 10 mL of distilled water and 5 mL of 30 wt% H2O2 solution were added to the mixture to complete the reaction. The resulting mixture was washed with a 5 wt% HCL deionized water solution until the pH reached 5-6 and dried at 50 °C in vacuum for 24 h to obtain GO.
[0026] (2-2) Preparation of GO-SH / MnO2: First, 5.0 g of 4-aminothiophenol and 80 mL of 1 M HCl solution were added to a three-necked flask, and the reaction temperature was raised to 50 °C under stirring until 4-aminothiophenol was completely dissolved. Then, NaNO2 solution (10.0 g of NaNO2 dissolved in 100 mL of deionized water) was added dropwise to the reaction mixture under ice bath -50 °C until the bubbles completely disappeared. After that, 5.0 g of GO was dispersed in 200 mL of deionized water and then added to the above solution. After stirring for 12 h under ice bath, the mixture was washed with acetone, ethanol and deionized water. Finally, GO-SH was obtained by vacuum drying at 50 °C for 24 h. 2.0 g of GO-SH was ultrasonically dispersed in 100 mL of pure water, 20 mL of potassium permanganate solution (15 mg / L) was added dropwise under stirring, and then 12 mL of formamide was added and ultrasonicated for 30 min. The precipitate was collected by centrifugation, washed three times with pure water, and dried in an oven for 12 h to obtain GO-SH / MnO2.
[0027] (2-3) Preparation of nano-CS / AgNPs: First, 2 g of CS was dissolved in 200 mL of acetic acid aqueous solution (0.1 wt%) and stirred in an oil bath. During the stirring process, 10 mL of freshly prepared AgNO3 (5 mg / mL) solution was added dropwise. After stirring and heating to 95 °C, 0.1 g / mL of NaOH solution was added dropwise until the solution turned yellow. The reaction was terminated after stirring at 95 °C for 20 min. The precipitate was collected by centrifugation, and the product was washed three times with deionized water. The product was then dried in vacuo at 60 °C for 1 h to obtain CS / AgNPs.
[0028] (2-4) Preparation of GO-SH / MnO2 / CS / AgNPs: 1 g of GO-SH / MnO2 was dispersed in 250 ml of deionized water, and then 2 g of nano-CS / AgNPs was added to the suspension and magnetically stirred at room temperature for 5 h. The mixture was then washed three times with deionized water and centrifuged. After centrifugation, the product was vacuum dried at 70 °C for 12 h to obtain GO-SH / MnO2 / CS / AgNPs.
[0029] (3) Preparation of open-cell breathable antibacterial EVA foam material: (3-1) adding 1 part of composite antibacterial auxiliary agent, 2.5 parts of AC foaming agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant, and 0.2 parts of release agent into an internal mixer and mixing together with the melt blend obtained in step (1) in an internal mixer at 130° C. for 10 minutes; (3-2) The blend obtained in step (3-1) is pressed into a thin sheet by an open mill and then transferred into a flat vulcanizer for compression foaming. The upper and lower template temperatures are both set to 150°C, the pressure is 10 MPa, and the molding time is 600 s. Pre-foaming is performed once. The pre-foamed semi-finished product is placed in a 60°C forced air drying oven and dried for 12 h. Then, the upper and lower template temperatures are adjusted to 175°C, the pressure is 15 MPa, and the molding time is 380 s. Secondary foaming is performed. After the mold is opened, the breathable and antibacterial EVA foam material automatically pops out.
[0030] Example 2 (1) Preparation of polymer matrix: same as in Example 1 (2) Preparation of GO-SH / MnO2 / CS / AgNPs: Same as Example 1 (3) Preparation of open-cell breathable antibacterial EVA foam material: (3-1) adding 2 parts of composite antibacterial auxiliary agent, 2.5 parts of AC foaming agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant, and 0.2 part of release agent into an internal mixer and mixing together with the melt blend obtained in step (1) in an internal mixer at 130° C. for 10 minutes; (3-2) The blend obtained in step (3-1) is pressed into a thin sheet by an open mill and then transferred into a flat vulcanizer for compression foaming. The upper and lower template temperatures are both set to 150°C, the pressure is 10 MPa, and the molding time is 600 s. Pre-foaming is performed once. The pre-foamed semi-finished product is placed in a 60°C forced air drying oven and dried for 12 h. Then, the upper and lower template temperatures are adjusted to 175°C, the pressure is 15 MPa, and the molding time is 380 s. Secondary foaming is performed. After the mold is opened, the breathable and antibacterial EVA foam material automatically pops out.
[0031] Example 3 (1) Preparation of polymer matrix: same as in Example 1 (2) Preparation of GO-SH / / MnO2 / CS / AgNPs: Same as Example 1 (3) Preparation of open-cell breathable antibacterial EVA foam material: (3-1) adding 3 parts of composite antibacterial auxiliary agent, 2.5 parts of AC foaming agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant, and 0.2 part of release agent into an internal mixer and mixing together with the melt blend obtained in step (1) in an internal mixer at 130° C. for 10 minutes; (3-2) The blend obtained in step (3-1) is pressed into a thin sheet by an open mill and then transferred into a flat vulcanizer for compression foaming. The upper and lower template temperatures are both set to 150°C, the pressure is 10 MPa, and the compression time is 600 s. Pre-foaming is performed once. The pre-foamed semi-finished product is placed in a 60°C forced air drying oven and dried for 12 h. Then, the upper and lower template temperatures are both adjusted to 175°C, the pressure is 15 MPa, and the compression time is 380 s. Secondary foaming is performed. After the mold is opened, the breathable and antibacterial EVA foam material automatically pops out.
[0032] Comparative Example 1 (without GO-SH / MnO2 / CS / AgNPs antibacterial agent) (1) Preparation of polymer matrix: same as in Example 1 (2) Preparation of open-cell breathable antibacterial EVA foam material: (2-1) adding 2.5 parts of AC foaming agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant, and 0.2 part of release agent paraffin into an internal mixer and mixing together with the melt blend obtained in step (1) in an internal mixer at 130° C. for 10 minutes; (2-2) The blend obtained in step (2-1) is pressed into a thin sheet by an open mill and then transferred into a flat vulcanizer for compression foaming. The upper and lower template temperatures are both set to 150°C, the pressure is 10 MPa, and the molding time is 600 s. Pre-foaming is performed once. The pre-foamed semi-finished product is placed in a 60°C forced air drying oven and dried for 12 h. Then, the upper and lower template temperatures are both adjusted to 175°C, the pressure is 15 MPa, and the molding time is 380 s. Secondary foaming is performed. After the mold is opened, the breathable and antibacterial EVA foam material automatically pops out.
[0033] Comparative Example 2 (GO-SH / MnO2 and CS / AgNPs were added to the system separately without any composite treatment) (1) Preparation of polymer matrix: same as in Example 1 (2) Preparation of GO-SH / MnO2 and CS / AgNPs: Same as Example 1 (3) Preparation of open-cell breathable antibacterial EVA foam material: (3-1) 1 part of GO-SH / MnO2 and CS / AgNPs mixed in a mass ratio of 1:2, 2.5 parts of AC foaming agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant, and 0.2 part of release agent were added to an internal mixer and the melt blend obtained in step (1) was continuously kneaded in an internal mixer at 130°C for 10 min; (3-2) The blend obtained in step (3-1) is pressed into a thin sheet by an open mill and then transferred into a flat vulcanizer for compression foaming. The upper and lower template temperatures are both set to 150°C, the pressure is 10 MPa, and the molding time is 600 s. Pre-foaming is performed once. The pre-foamed semi-finished product is placed in a 60°C forced air drying oven and dried for 12 h. Then, the upper and lower template temperatures are adjusted to 175°C, the pressure is 15 MPa, and the molding time is 380 s. Secondary foaming is performed. After the mold is opened, the breathable and antibacterial EVA foam material automatically pops out.
[0034] Comparative Example 3 (GO is composited with MnO2 and CS / AgNPs according to the above method, but GO is not thiol-modified) (1) Preparation of polymer matrix: same as in Example 1 (2) Preparation of GO / MnO2 / CS / AgNPs: (2-1) Preparation of GO and CS / AgNPs: Same as Example 1 (2-2) Preparation of GO / MnO2 / CS / AgNPs: 2.0 g of GO was ultrasonically dispersed in 100 mL of pure water, and 20 mL of potassium permanganate solution (15 mg / L) was added dropwise under stirring. Then 12 mL of formamide was added and ultrasonicated for 30 min. The precipitate was collected by centrifugation, washed three times with pure water, and dried in an oven for 12 h to obtain GO / MnO2. 1 g of GO / MnO2 was dispersed in 250 ml of deionized water, and then 2 g of nano-CS / AgNPs was added to the suspension, magnetically stirred at room temperature for 5 h, and then the mixture was washed with deionized water. After centrifugation, the product was vacuum dried at 70 °C for 12 h to obtain GO / MnO2 / CS / AgNPs.
[0035] (3) Preparation of open-cell breathable antibacterial EVA foam material: (3-1) adding 1 part of GO / MnO2 / CS / AgNPs, 2.5 parts of AC foaming agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant, and 0.2 part of release agent into an internal mixer and mixing together with the melt blend obtained in step (1) in an internal mixer at 130°C for 10 min; (3-2) The blend obtained in step (3-1) is pressed into a thin sheet by an open mill and then transferred into a flat vulcanizer for compression foaming. The upper and lower template temperatures are both set to 150°C, the pressure is 10 MPa, and the molding time is 600 s. Pre-foaming is performed once. The pre-foamed semi-finished product is placed in a 60°C forced air drying oven and dried for 12 h. Then, the upper and lower template temperatures are adjusted to 175°C, the pressure is 15 MPa, and the molding time is 380 s. Secondary foaming is performed. After the mold is opened, the breathable and antibacterial EVA foam material automatically pops out.
[0036] Comparative Example 4 (GO-SH and CS / AgNPs were composited according to the above method, but without adding MnO2) (1) Preparation of polymer matrix: same as in Example 1 (2) Composite of nano-CS / AgNPs and GO-SH: (2-1) Preparation of GO-SH: Same as Example 1 (2-2) Preparation of CS / AgNPs: Same as Example 1 (2-3) Preparation of GO-SH / CS / AgNPs: 1 g of GO-SH was dispersed in 250 ml of deionized water, and then 2 g of nano-CS / AgNPs was added to the suspension and magnetically stirred at room temperature for 5 h. The mixture was then washed with deionized water and centrifuged. The product was vacuum dried at 70 °C for 12 h to obtain GO-SH / CS / AgNPs.
[0037] (3) Preparation of open-cell breathable antibacterial EVA foam material: (3-1) adding 1 part of GO-SH / CS / AgNPs, 2.5 parts of AC foaming agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant, and 0.2 part of release agent into an internal mixer and mixing together with the melt blend obtained in step (1) in an internal mixer at 130° C. for 10 min; (3-2) The blend obtained in step (3-1) is pressed into a thin sheet by an open mill and then transferred into a flat vulcanizer for compression foaming. The upper and lower template temperatures are both set to 150°C, the pressure is 10 MPa, and the molding time is 600 s. Pre-foaming is performed once. The pre-foamed semi-finished product is placed in a 60°C forced air drying oven and dried for 12 h. Then, the upper and lower template temperatures are adjusted to 175°C, the pressure is 15 MPa, and the molding time is 380 s. Secondary foaming is performed. After the mold is opened, the breathable and antibacterial EVA foam material automatically pops out.
[0038] Comparative Example 5 (not using the crystallization temperature difference method and the secondary foaming method) (1) Preparation of polymer matrix: 90 parts of EVA, 10 parts of POE-g-MAH, and 1.5 parts of cross-linking agent were placed in an internal mixer preheated at 130°C and blended for 10 min at a speed of 30 rpm; (2) Preparation of GO-SH / / MnO2 / CS / AgNPs: Same as Example 1 (3) Preparation of open-cell breathable antibacterial EVA foam material: (3-1) adding 1 part of composite antibacterial auxiliary agent, 2.5 parts of AC foaming agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant, and 0.2 parts of release agent into an internal mixer and mixing together with the melt blend obtained in step (1) in an internal mixer at 130° C. for 10 minutes; (3-2) The blend obtained in step (3-1) is pressed into a thin sheet using an open mill and then transferred into a flat-plate vulcanizer for compression foaming. The upper and lower mold plate temperatures are both 175° C., the pressure is 15 MPa, and the compression time is 380 s. The foaming is performed, and the breathable and antibacterial EVA foam material automatically pops out after the mold is opened.
[0039] The samples obtained in the embodiments and comparative examples were subjected to performance tests.
[0040] Table 1: Performance Test Table 2: Sample luminescence value test Table 3: Sample antibacterial rate test Antibacterial performance test method and steps: self-made fluorescent Escherichia coli was used to conduct anti-luminescent Escherichia coli verification experiments at different locations of the sample for 5min, 30min, and 60min. The test method is: 500μL of luminescent bacteria solution was dripped at different locations of the sample, and 200μL was taken after a specified time to test the change in the average luminescence value. The schematic diagram is shown in the figure. Figure 4 . (Luminescent bacteria range 3.0×10 6 ~6.0×10 6 cfu / mL) to test the luminescence value and calculate the inhibition rate. The results are shown in Tables 2 and 3 (Comparative Example 1 is used as the control group).
[0041] From the test results in Table 1, in Example 1 and Comparative Example 5, after the EVA foam is not made into an open-cell structure, the mechanical properties of the product show a slight upward trend. This is because the closed-cell structure connects the pore walls to each other, which can improve the mechanical properties of the foam, but the open porosity shows a significant downward trend, indicating that after the material is made into an open-cell structure, the open porosity is significantly improved, so that the air circulation rate of the product is enhanced and the air permeability is improved. In Examples 1-3, with the increase of the content of the composite antibacterial additive, the tensile strength, pore density, hardness, and elongation at break of the product all show an upward trend, the rebound performance is slightly reduced, and most of the mechanical properties are improved. The performance of Example 1 without adding the composite antibacterial additive is better, and the addition of the antibacterial additive filler improves the hardness of the material, which slightly reduces the resilience and compression deformation of the material. Compared with Example 1, the opening rate of Example 1 is slightly reduced due to the addition of the GO-SH / MnO2 / CS / AgNPs composite antibacterial additive, indicating that the GO-SH / MnO2 / CS / AgNPs composite antibacterial additive has a good modification effect on the mechanical properties of the foaming material, and has little effect on the resilience, opening rate and compression deformation of the foaming material, and the composite antibacterial additive has good compatibility with the resin matrix. Observing the data of Comparative Example 2, compared with Example 1, the mechanical properties and foaming properties (opening rate) of Comparative Example 2 are greatly reduced, and most of the mechanical performance parameters of Comparative Example 2 are reduced instead of increased compared with Comparative Example 1 without adding the modifier. This is because both nano CS / AgNPs and graphene oxide have high surface energy, and the particles agglomerate significantly without any surface treatment. After the composite material is constructed, the surface energy is greatly reduced, which is more conducive to the dispersion of the antibacterial additive in the resin matrix, so the modification effect of the composite antibacterial additive is better. The graphene oxide in Comparative Example 3 has not been modified by thiol group, and the degree of composite between CS / AgNPs nanoparticles and the graphene oxide matrix is reduced. Due to the influence of the surface energy in the material, the degree of dispersion of the composite additive in the matrix is not as good as that in Example 1. The mechanical properties and foaming properties (opening rate) of the obtained product are greatly reduced compared with Example 1. The mechanical properties and foaming properties of Comparative Example 4 are not significantly different from those of Example 1.
[0042] From the test results in Table 2 and Table 3, compared with the comparative example 1 without adding any antibacterial agent, from Example 1 to Example 3, with the increase of the content of the composite antibacterial auxiliary agent, the antibacterial ability of the samples at 5min, 10min, and 60min increased significantly, indicating that GO-SH / MnO2 / CS / AgNPs has good antibacterial effect and good compatibility with the matrix. Observing the data of Comparative Example 2, GO-SH / MnO2 and CS / AgNPs are added to the matrix without composite treatment, and they react and play a role respectively during the banburying process, and the polyhydroxy polymer graphene oxide and CS / AgNPs with high surface energy are prone to agglomeration during the melting process, so the antibacterial effect is far less ideal than first composite and then added to the matrix for melting; while Comparative Example 3 only composites graphene oxide with MnO2 and CS / AgNPs. Due to the lack of interaction between thiol groups and CS / AgNPs nanoparticles, there is still a part of self-aggregation, and the antibacterial agent is far less stable in structure than GO-SH / MnO2 / CS / AgNPs containing thiol bonds, so the antibacterial effect is not as good as GO-SH / MnO2 / CS / AgNPs, which shows that the thiol functionalization of GO in the composite antibacterial agent can maximize the antibacterial effect. Comparative Example 4 uses GO-SH and CS / AgNPs to construct a composite material but does not add MnO2. The lack of MnO2 as a catalyst to decompose the H2O2 environment that is conducive to bacterial growth makes the material inferior to GO-SH / MnO2 / CS / AgNPs in inhibiting bacterial growth and destroying the bacterial growth environment. The antibacterial performance is significantly reduced compared with Example 1.
[0043] Figure 1 Fourier infrared image of the powder of GO-SH / MnO2 / CS / AgNPs composite antibacterial additive, where 3460 cm -1 The -OH vibration peaks of CS / AgNPs and GO-SH are present at 2920 cm -1 The absorption peak at 2540 cm is the stretching vibration peak of the alkyl group. -1 The absorption peak at 1632cm is the vibration peak of -SH. -1 The characteristic peak at 1390cm corresponds to the stretching vibration of the C=C bond of the carbon skeleton and may also belong to the bending vibration absorption peak of C-OH. -1 and 1352cm -1 The band observed at 1141 cm is caused by the shear vibration of the -NH2 group and the stretching vibration of the glycosidic bond of the polymer. -1 The absorption peak at 506 cm is the antisymmetric vibration of COC, and the characteristic peak of MnO2 is at 506 cm -1 The symmetric stretching vibration of Mn-O bond is shown in Fig.
[0044] Figure 2This is the SEM image of the composite material. It can be seen that nano-CS / AgNPs are evenly dispersed on the GO matrix after thiol modification, which proves that the introduction of thiol groups in the GO matrix plays an important role in preventing the agglomeration of nanoparticles.
[0045] Figure 3 The SEM image of open-cell bubbles shows that the pore structure is mostly open-cell. First, when the soft cross-section of the low-Tc polymer (LDPE) forms a smaller dispersed phase and the hard cross-section of the high-Tc polymer (EVA) forms the main melt matrix, the pore opening can be initiated and propagated by well-dispersed low-Tc polymer domains, which are surrounded by growing adjacent bubbles. These soft domains can be extended as the bubbles grow, that is, the pore wall becomes thinner until it breaks to form an open-cell structure.
[0046] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A breathable and antibacterial EVA foam material, characterized in that: The raw materials of the EVA foaming material include, by weight: 70 parts of EVA, 20 parts of LDPE, 10 parts of POE-g-MAH, 1-3 parts of composite antibacterial additives, 2.5 parts of AC foaming agents, 1.5 parts of cross-linking agents, 2.5 parts of fillers, 3 parts of calcium zinc stabilizers, 1 part of lubricant, and 0.2 parts of release agents.
2. The breathable and antibacterial EVA foam material according to claim 1, characterized in that: The composite antibacterial additive is GO-SH / MnO2 / CS / AgNPs, and its preparation steps include: (1) Preparation of GO-SH: First, 5 g of 4-aminothiophenol and 80 mL of 1 M HCl solution were added to a three-necked flask, and the reaction temperature was raised to 50 °C under stirring until 4-aminothiophenol was completely dissolved. Then, 1.5 mol / L NaNO2 solution was added dropwise to the reaction mixture under ice bath conditions until the bubbles disappeared completely. After that, a deionized water dispersion containing 5 g of graphene oxide GO was added, and after stirring for 12 h under ice bath conditions, it was washed with acetone, ethanol and deionized water. Finally, GO-SH was obtained by vacuum drying at 50 °C for 24 h. (2) Preparation of CS / AgNPs: 2 g of chitosan CS was dissolved in 200 mL of 0.1 wt% acetic acid aqueous solution, placed in an oil bath and stirred. During the stirring process, 10 mL of freshly prepared 5 mg / mL AgNO3 solution was added dropwise. After stirring and heating to 95 °C, 0.1 g / mL NaOH solution was added dropwise until the solution turned yellow. The reaction was terminated after stirring at 95 °C for 20 min. The precipitate was collected by centrifugation, and the product was washed three times with deionized water. The product was then vacuum dried at 60 °C for 1 h to obtain CS / AgNPs. (3) Preparation of GO-SH / MnO2 / CS / AgNPs: 2 g GO-SH was ultrasonically dispersed in 100 mL pure water, and 20 mL of 15 mg / L potassium permanganate solution was added dropwise under stirring. Then, 12 mL of formamide was added and ultrasonicated for 30 min. The precipitate was collected by centrifugation, washed three times with pure water, and dried in an oven for 12 h to obtain GO-SH / MnO2. GO-SH / MnO2 was then dispersed in deionized water, and CS / AgNPs were added. The mixture was magnetically stirred at room temperature for 5 h, and then washed three times with deionized water. After centrifugation, the product was vacuum dried at 70 °C for 12 h to obtain GO-SH / MnO2 / CS / AgNPs.
3. The breathable and antibacterial EVA foam material according to claim 1, characterized in that: The mass ratio of GO-SH / MnO2 and CS / AgNPs in step (3) is 1:
2.
4. The breathable and antibacterial EVA foam material according to claim 1, characterized in that: The filler is one or more of nano zinc oxide and zinc stearate.
5. The breathable and antibacterial EVA foam material according to claim 1, characterized in that: The cross-linking agent is dicumyl peroxide.
6. The breathable and antibacterial EVA foam material according to claim 1, characterized in that: The lubricant is one or more of stearic acid, butyl stearate and oleamide.
7. The breathable and antibacterial EVA foam material according to claim 1, characterized in that: The preparation of POE-g-MAH comprises: weighing 0.4 parts by weight of maleic anhydride, dissolving the maleic anhydride in acetone to prepare a solution; weighing 4 parts by weight of polyolefin elastomer POE particles, spraying the maleic anhydride acetone solution into the POE particles, mixing them evenly in a high-speed mixer, and standing to volatilize the acetone; the mixed materials are melt-blended for 10 minutes using a torque rheometer, the rotor speed is 30 r / min, the torque temperature is 165°C, and after the blending is completed, the melt is melted into sheets in an open mill.
8. The method for preparing the breathable and antibacterial EVA foam material according to any one of claims 1 to 7, characterized in that: The EVA foam material is an open-cell structure, and the preparation steps include: melt-blending EVA and LDPE, two materials with a large difference in crystallization temperature, wherein the melt structure contains two blended polymers with different crystallization temperature values, and the high crystallization temperature polymer will crystallize before the low crystallization temperature polymer, thereby generating pressure on the pore structure to cause the pores to rupture and connect to generate an open-cell structure, and at the same time, using a secondary foaming method as a compression foaming method to prepare the EVA foam material into an open-cell pore structure.
9. The method for preparing the breathable and antibacterial EVA foam material according to claim 8, characterized in that: 70 parts of EVA, 20 parts of LDPE, 10 parts of POE-g-MAH, 1-3 parts of composite antibacterial additives, 2.5 parts of AC foaming agent, 1.5 parts of cross-linking agent, 2.5 parts of filler, 3 parts of calcium zinc stabilizer, 1 part of lubricant and 0.2 parts of release agent are put into an internal mixer for blending, and then the blended product is subjected to cold and hot compression molding.
10. The method for preparing the breathable and antibacterial EVA foam material according to claim 9, characterized in that: The following steps are involved: 1) Put EVA, LDPE, POE-g-MAH and cross-linking agent into an internal mixer preheated at 130°C and blend for 10 min to obtain blend 1. The speed of the internal mixer is 30 rpm. 2) adding the composite antibacterial auxiliary agent, AC foaming agent, filler, calcium zinc stabilizer, lubricant and release agent to blend 1, and continuing to mix in an internal mixer at 130° C. for 10 min to obtain blend 2; 3) After blend 2 is pressed into a thin sheet by an open mixing mill, it is transferred into a flat vulcanizer for compression foaming. The upper and lower template temperatures are both set to 150°C, the pressure is 10 MPa, and the compression time is 600 s for a pre-foaming process. The pre-foamed semi-finished product is placed in a 60°C forced air drying oven and dried for 12 h. Then, the upper and lower template temperatures are adjusted to 175°C, the pressure is 15 MPa, and the compression time is 380 s for a secondary foaming process. After the mold is opened, the breathable and antibacterial EVA foam material automatically pops out.
Citation Information
Patent Citations
Preparation of anti-ultraviolet ageing and antimicrobial wood-plastic composite material filled and modified with chitosan modified silver nanoparticles
CN108948769A
Graphene-foam EVA composite material and preparation method thereof
CN109161085A
Graphene regenerated EVA foam insole and preparation method thereof
CN110092978A
Chitosan / manganese dioxide / glucose oxidase nano composite material as well as preparation and application thereof
CN114984241A
Graphene oxide / iron oxide / chitosan nanocomposite
KR101443714B1